The use of layered model when implementing E-learning - E. S. Rogalsky (Цифровая трансформация)
E-learning creates and continues to actively develop new type of learning due to the organization of the educational process, typical for the third stage of development of the educational institutions of mankind. Creating cloud-based virtual educational enviroment is an example of creating a model for understanding the problems of analysis and design of e-learning.